Sulfur isotope evolution in sulfide ores from Western Alps: Assessing the influence of subduction-related metamorphism - Giacometti, F.; Evans, Katy; Rebay, G.; Cliff, J.; Tomkins, A.; Rossetti, P.; Vaggelli, G.; Adams, D. (American Geophysical Union, 2014)
Sulfides entering subduction zones can play an important role in the release of sulfur and metals to the mantle wedge and contribute to the formation of volcanic arc-associated ores. Fractionation of stable sulfur isotopes recorded by sulfides during metamorphism can provide evidence of fluid-rock interactions during metamorphism and give insights on sulfur mobilization. A detailed microtextural and geochemical study was performed on mineralized samples from two ocean floor-related sulfide deposits (Servette and Beth-Ghinivert) in high-pressure units of the Italian Western Alps, which underwent different metamorphic evolutions. The combination of microtextural investigations with d34S values from in situ ion probe analyses within individual pyrite and chalcopyrite grains allowed evaluation of the effectiveness of metamorphism in modifying the isotopic record and mobilizing sulfur and metals and have insights on fluid circulation within the slab. Textures and isotopic compositions inherited from the protolith are recorded at Beth-Ghinivert, where limited metamorphic recrystallization is attributed to limited interaction with metamorphic fluids. Isotopic modification by metamorphic processes occurred only at the submillimeter scale at Servette, where local interactions with infiltrating hydrothermal fluid are recorded by metamorphic grains. Notwithstanding the differences recorded by the two deposits, neither underwent intensive isotopic reequilibration or records evidence of intense fluid-rock interaction and S mobilization during metamorphism. Therefore, subducted sulfide deposits dominated by pyrite and chalcopyrite are unlikely to release significant quantities of sulfur to the mantle wedge and to arc magmatism sources at metamorphic grades below the lower eclogite facies.